Optimizing Straw and Manure Co-Substitution Regimes to Maintain Stable Crop Yields Through Enhanced Soil Stoichiometric Balance - Peipei Li; Yuanyi Shang; Hui Li; Fang Li; Yi Wang; Xueqiang Zhu; Shiying Li; Xiaolin Wang; Yanlai Han (Agriculture)
The benefits of partially substituting inorganic fertilizers with organic fertilizers have been extensively acknowledged. However, the key mechanisms behind nutrient transformation and supply for stable crop yields are still not fully understood. Based on an 11-year field experiment with a wheat–maize rotation system, this study explored the advantages of combined straw and manure substitution under various organic substitution regimes. These regimes included an unfertilized control (CK), inorganic nitrogen, phosphorus, and potassium fertilizers (NPK), NPK substituted with straw (NPKS), NPK substituted with manure (NPKM), and NPK substituted with both straw and manure (NPKSM). Compared to NPK and NPKS, NPKM and NPKSM significantly improved wheat yield by 12.8% and 13.8%, respectively. Bulk soil organic carbon (SOC), total nitrogen (TN), available superphosphate (AP), β-glucosidase (βG), urease (URE), and alkaline phosphatase (ALP) were all higher in the NPKM treatment than in the NPKSM treatment. However, compared to NPKM, NPKSM significantly decreased the potential nitrification rate by 31.0% and increased the soil NH4+-N content. Correspondingly, the functional genes of nitrification were also found to be decreased in the NPKSM treatment. In the rhizosphere, most soil factors increased compared to bulk soil, but treatment differences were smaller. However, the differences among treatments were reduced in the rhizosphere. The high amount of manure applied in the NPKM treatment caused excessive soil phosphorus accumulation, reaching over 46.7 mg/kg, resulting in lower N/P and C/P ratios. The soil quality index (SQI), based on soil nutrients, enzymes, functional genes, and C:N:P stoichiometry, was 9.9% higher in NPKSM than in NPKM. Bulk soil SQIs showed stronger correlations with wheat yields than rhizosphere SQIs, highlighting that bulk soil was superior to rhizosphere in predicting crop yield. Partial least squares path modeling showed that C/N, N/P, and C/P ratios strongly influenced SQIs. The NPKSM treatment, which improved soil nutrients, biological factors, and balanced C:N:P stoichiometry, is an effective strategy for sustainable agriculture. Future practices should focus on maintaining stoichiometric balance to sustain soil quality and crop yields.